EVALUATION OF LAND SUITABILITY FOR INCREASING PRODUCTIVITY IN DEGRADED UNDA WATERSHED, DISTRICT OF KARANGASEM, BALI - Trigunasih, Ni Made; Merit, I Nyoman; Wiyanti, Wiyanti; Narka, I Wayan; Dibia, I Nyoman (International Journal of Biosciences and Biotechnology; Vol 5 No 1 (2017), 2017)
Evaluation of land suitability to increase the productivity of degraded lands in the Unda watershed aims: providing a database of land suitability for land use planning in support of sustainable agricultural development, providing spatial information, and recommendations in accordance with the land use plan of inhibiting factors that exist. Identification of characteristic land quality evaluation survey carried out by the method of land with exploration area of research followed by soil sampling at some sample of land units. Land suitability classification using the criteria of the Technical Guidelines for Evaluation of Land For Agricultural Commodities of Soil Research Institute (2003) is by matching between the haracteristics of the land with the requirements of growing plants was evaluated. Types of agricultural crops that are evaluated include plantation crops and food crops hotikultura fruits. Suitability actual land (land suitability based on survey data) are mostly classified as unsuitable (N), and marginally suitable (S3). Qualities/characteristics as the land that is the main limiting factor, among others: quality of land erosion, slope, water availability, temperature, rooting media (soil texture and coarse material). Sustainable land use planning can be recommended with agroforestry, accompanied by vegetative conservation measures because it is cheaper and easier to be carried out by farmers. Recommended cultivation effort is a combination of timber plants with horticultural crops of fruits with the provisions of at least 40% must be enclosed timber. Plant timber that can be developed between the other plants that are not too heavy canopy.